Eksistensi Mamak Kanduang dalam Perkawinan Kemenakan - sri Wahyuni; Desi Fitria; Arisman Sabir (IJOCE: Indonesia Journal of Civic Education, 2022)
This study aims to see how the role of mamak kanduang in the marriage of a nephew in the Padang Pariaman community, West Sumatra, which is part of the local wisdom of the Minangkabau community. This research uses a descriptive method with a qualitative approach. Data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis techniques by means of data collection, data reduction and data presentation. The results showed that the existence of mamak kanduang in a nephew's marriage in Padang Pariaman played more roles as matchmakers (Maresek), proposed marriage, bakampuang-kampuang activities and deliberating the amount of japuiktan money. The conclusions of the study that the role of mamak kanduang in the marriage of nephews are a) The role of mamak kanduang in finding a mate or Maresek in marriage; b) The role of mamak kanduang in proposing; c) The role of mamak kanduang in bakampuang-village activities and deliberating the amount of japuiktan money. Keywords: Mamak, Marriage, Role.